Poeta necans: the metalepsis of killing a character in diachronic perspective - Kuhn-Treichel, Thomas (Narrative, 2024)
This essay traces expressions in which authors or narrators claim to or are said to kill a character, with the key question as to which ideas about storytelling the cases convey and how these ideas resemble or differ across different periods. Examples of the "poeta necans metalepsis" are found in ancient Greek literature all the way to the modern novel; however, they bear a remarkable variety of implications. Already in antiquity, we find a range of positive to outright derisory usages, which are united by the fact that they present killing as a natural and unquestioned task of authors, especially for epic poets. From the Renaissance onwards, the picture changes: Ariosto exposes the idea that a narrator should save rather than slay his characters, and in the past two centuries, narrators reflecting on their qualms about putting a character to death becomes all but the standard case. The essay works with case studies from different eras, with emphasis on early usages in antiquity, which are analyzed according to the principles of diachronic narratology. In this way, the essay sheds light not only on historical concepts of storytelling but also on the motif of death in literature, which, as is argued, is not a negation of life but rather supports and defends it in various ways, for the narrator, the audience, and the characters.